(untitled) (Journal of the College of Basic Education, 2026)
Television drama is an art form that relies on reality and society in general as its raw material. This drama attempts to penetrate, reveal, and analyze human society, as well as select a set of events related to society and influenced by changes in time or place. This is what attracted the researcher’s attention, leading him to choose the title of his research: (Social Values ​​in Television Drama After 2003: The Hotel Series as a Model). The theoretical framework of this research is based on the following: Chapter One (Methodological Framework): This chapter includes the research problem, which is expressed in the following question: What is the nature of social values ​​in Iraqi television drama after 2003? It also includes the importance of the research, its objectives, its limitations, and a definition of terms. Chapter Two (Theoretical Framework): The research is divided into two sections as follows: Section One: Social Value and Visual Structure: This section examines the nature of social values ​​and how they are employed in visual structure through the use of elements of cinematic language. Section Two: Iraqi Television Drama: In this section, the researcher examines Iraqi television drama as a historical introduction, as well as the nature of the themes and events it has addressed throughout its history since 2003. The researcher developed a set of theoretical framework indicators which he adopted as tools for analyzing the research sample. Chapter Three (Research Procedures): This chapter includes the research methodology, the research population, the analytical tools, the research sample, and the analysis of the sample, which was the Iraqi television series "The Hotel," directed by Hassan Hosni and produced in 2019. Chapter Four (Results and Conclusions): After analyzing the sample, the researcher reached several conclusions, including: Iraqi drama after 2003 was replete with themes and events that addressed social and religious issues with a boldness in their presentation, such as moral deviance, homosexuality, rape, human trafficking, and police corruption. This was evident in the research sample, specifically the Iraqi drama series "The Hotel." The researcher then presented a set of conclusions and concluded the research with a list of the sources he used.